THE ORIGIN, COMPOSITION AND RATES OF ORGANIC NITROGEN DEPOSITION: A MISSING PIECE OF THE NITROGEN CYCLE? - Neff Ja.C.; Holland E.A.; Dentener F.J.; McDowell W.H.; Russell K.M. (My University, 2002)
Organic forms of nitrogen are widespread in the atmosphere and their deposition may constitute a substantive input of atmospheric N to terrestrial and aquatic ecosystems. Recent studies have expanded the pool of available measurements and our awareness of their potential significance. Here, we use these measurements to provide a coherent picture of the processes that produce both oxidized and reduced forms of organic nitrogen in the atmosphere, examine how those processes are linked to human activity and how they may contribute to the N load from the atmosphere to ecosystems. We summarize and synthesize data from 41 measurements of the concentrations and fluxes of atmospheric organic nitrogen (AON). In addition, we examine the contribution of reduced organic nitrogen compounds such as amino acids, bacterial/particulate N, and oxidized compounds such as organic nitrates to deposition fluxes of AON. The percentage contribution of organic N to total N loading varies from site to site and with measurement methodology but is consistently around a third of the total N load with a median value of 30% (Standard Deviation of 16%). There are no indications that AON is a proportionally greater contributor to N deposition in unpolluted environments and there are not strong correlations between fluxes of nitrate and AON or ammonium and AON. Possible sources for AON include byproducts of reactions between NOx and hydrocarbons, marine and terrestrial sources of reduced (amino acid) N and the long-range transport of organic matter (dust, pollen etc.) and bacteria. Both dust and organic nitrates such as PAN appear to play an important role in the overall flux of AON to the surface of the earth. For estimates of organic nitrate deposition, we also use an atmospheric chemical transport model to evaluate the spatial distribution of fluxes and the globally integrated deposition values. Our preliminary estimate of the magnitude of global AON fluxes places the flux between 10 and 50 Tg of N per year with substantial unresolved uncertainties but clear indications that AON deposition is an important aspect of local and global atmospheric N budgets and deserves further consideration.